2004
DOI: 10.1002/ijc.20297
|View full text |Cite
|
Sign up to set email alerts
|

Combretastatin family member OXI4503 induces tumor vascular collapse through the induction of endothelial apoptosis

Abstract: The mechanism of tumor cell killing by OXI4503 was investigated by studying vascular functional and morphological changes post drug administration. SCID mice bearing MHEC5-T hemangioendothelioma were given a single dose of OXI4503 at 100 mg/kg. Tumor blood flow, measured by microsphere fluorescence, was reduced by 50% at 1 hr, and reached a maximum level 6 -24 hr post drug treatment. Tumor vascular permeability, measured by Evan's blue and hemoglobin, increased significantly from 3 hr and peaked at 18 hr. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 35 publications
7
70
1
Order By: Relevance
“…6), this suggests that NOS inhibition is particularly effective in interacting with the downstream consequences of CA-4-P treatment. Several studies have shown that CA-4-P and related compounds induce increased tumor expression of hypoxia inducible factor-1α and angiogenic growth factors (44)(45)(46), as well as mobilizing endothelial progenitor cells from bone marrow (47). Others have shown that the combination of VDAs with antiangiogenic agents are particularly effective (48).…”
Section: Discussionmentioning
confidence: 99%
“…6), this suggests that NOS inhibition is particularly effective in interacting with the downstream consequences of CA-4-P treatment. Several studies have shown that CA-4-P and related compounds induce increased tumor expression of hypoxia inducible factor-1α and angiogenic growth factors (44)(45)(46), as well as mobilizing endothelial progenitor cells from bone marrow (47). Others have shown that the combination of VDAs with antiangiogenic agents are particularly effective (48).…”
Section: Discussionmentioning
confidence: 99%
“…Several CA-4 derivatives were described and patented as small molecule VDAs [42], including AVE 8062 and Oxi-4503 (Fig. 4), which demonstrate strong anti-tumor effects due to their vasculature-disrupting activity [90,91]. Ombrabulin enhances the efficacy of standard therapies (radiation plus cisplatin and radiation plus cetuximab) in head and neck squamous cell carcinoma (HNSCC) xenograft models.…”
Section: Tubulin-binding Stilbenes As Vdasmentioning
confidence: 99%
“…OXi4503, a Combretastatin family member, is a tubulin binding drug (27,28) and currently considered among the most potent VDAs (13,29). In this study, we employed spectral imaging of window chamber tumors to investigate the realtime VDA-induced modulation in microvessel structure and function of two different tumor types during multiple serial treatments with OXi4503.…”
Section: Discussionmentioning
confidence: 99%
“…Combretastatins, initially derived from the South African tree Combretum caffrum, represent a class of potent tubulin binding agents with significant vascular disrupting activity (5,8). Lead agents Combretastatin A4-P (CA4-P) and OXi4503 (CA1-P) have been shown to result in time-dependent decreases in tumor perfusion, increased tumor vascular permeability, and significant tumor vascular damage in a wide variety of preclinical tumor models (8,(11)(12)(13). In the clinic, these agents have now entered Phase II/III evaluation (14,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation